2010
DOI: 10.1002/adfm.200902149
|View full text |Cite
|
Sign up to set email alerts
|

Interface Modifications of InAs Quantum‐Dots Solids and their Effects on FET Performance

Abstract: InAs nanocrystals field‐effect transistors with an ON/OFF ratio of 105 are reported. By tailoring the interface regions in the active layer step‐by‐step, the evolution of the ON/OFF ratio can be followed from approximately 5 all the way to around 105. The formation of a semiconducting solid from colloidal nanocrystals is achieved through targeted design of the nanocrystal–nanocrystal interaction. The manipulation characteristics of the nanocrystal interfaces include the matrix surrounding the inorganic core, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…33,116,117 Also, the capping ligands frontier orbitals put a potential barrier at the CQD surface, rendering a slight normalization of the crystalline electronic energy levels. 118 Other studies indicated the ligands …”
Section: Functionality Of the Organic Ligandsmentioning
confidence: 99%
“…33,116,117 Also, the capping ligands frontier orbitals put a potential barrier at the CQD surface, rendering a slight normalization of the crystalline electronic energy levels. 118 Other studies indicated the ligands …”
Section: Functionality Of the Organic Ligandsmentioning
confidence: 99%
“…However, the inherently covalent bonding nature of InAs surfaces gravely challenges defect-controlled conductive InAs CQD layer fabrication via wet chemistry unlike ionic IV–VI CQDs. Integration of InAs CQDs into solid devices has been attempted mostly in field-effect transistors (FETs) 15 17 using rather large-sized CQDs with small bandgaps. More seriously, fabrication of FET devices employing InAs CQD films generally involves a high-temperature annealing process from 250 to 300 °C, and depositions are performed in a nitrogen-filled glove box 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Integration of InAs CQDs into solid devices has been attempted mostly in field-effect transistors (FETs) 15 17 using rather large-sized CQDs with small bandgaps. More seriously, fabrication of FET devices employing InAs CQD films generally involves a high-temperature annealing process from 250 to 300 °C, and depositions are performed in a nitrogen-filled glove box 15 17 . Such processes have not yet met the various requirements of emerging PV technologies such as deposition of CQDs on flexible substrates via an inexpensive solution process and compatibility with high-speed roll-to-roll printing.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of chemical units such as bifunctional organic molecules, inorganic molecules, single ions, and metal chalcogenide complexes have been used as ligands for QD thin films. ,, Cd- and Pb-based QDs have been extensively studied, and their passivation methods are well-developed to minimize surface imperfections. In fact, Cd- and Pb-chalcogenide QD solid films have shown excellent electronic qualities that are suitable for existing conventional devices. ,, These are attributed to their ionic bonding characters that are highly tolerant to the in-gap states (IGS) when the global charge neutrality or chemical stoichiometry is satisfied. ,, Unfortunately, Cd- and Pb-based QD devices are frequently prohibited for some commercial uses by restriction of hazardous substances directives, owing to their potential harmful effects on health and the environment. , Accordingly, there is a high demand for alternative materials that do not involve heavy metal ions for practical applications. On one hand, among various candidates, III–V QDs such as InP or InAs have been mostly considered owing to their relatively low toxicity as well as their optical characteristics being comparable to Cd- or Pb-based QDs. On the other hand, III–V QDs are easily oxidized and present weak electronic tolerance to surface defects due to their high covalent character. , In brief, it is intrinsically more challenging to handle III–V QDs and to improve their quality to acceptable levels.…”
mentioning
confidence: 99%